Solid dispersion systems engineered from hydroxypropyl‐β‐cyclodextrin and water‐soluble polymers for enhanced oral bioavailability of nimodipine. (29th May 2020) - Boakye‐Yiadom, Kofi Oti; Kesse, Samuel; Aquib, Md; Filli, Mensura Sied; Farooq, Muhammad Asim; Wang, Bo
Abstract : Nimodipine (NMD) is a calcium channel blocker that is used in the treatment of cerebrovascular disorders, such as stroke indicated for biological rhythm and neurological disorders. According to biopharmaceutical classification, NMD is categorized as a class ΙΙ drug, meaning it has a poor solubility profile. The objective of this experiment is to prepare multicomponent systems to enhance the solubility, dissolution, and bioavailability of NMD. Inclusion complex and solvent evaporation techniques have been exploited to overcome this challenge. in vitro dissolution studies and solubility, the profile was performed in three pH media (pH 7.5, 1.2, and 6.8). The drug release at (Q60min ) for SD‐PVP3 was 33‐fold higher than pure NMD in double‐distilled water. The solubility of SD PVP3 was about 30 times higher than plain NMD in double‐distilled water. A pharmacokinetic study in rats indicated that the AUC0‐720 value of the inclusion complex (NMD‐KD) was 1.63‐fold higher than pure NMD. At the same time, the solid dispersion (NMD‐SD PVP3) was 3.94‐fold higher than that of plain NMD, indicating a significant increase in the bioavailability of NMD. The combination of the inclusion complex and solvent evaporation method led to the formation of new solid dispersions (SD PLX and SD PVP), which significantly increased the solubility, dissolution, and the oral bioavailability of NMD.